Inverse Exponentiated Odd Lomax Exponential Distribution: Properties and Applications - Chaudhary, Arun Kumar; Telee, Lal Babu Sah; Kumar, Vijay (Nepalese Journal of Statistics, 2022)
Mentioned in manuscript abstract.